2010
DOI: 10.1111/j.1745-4514.2010.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Lipid Oxidation in Breast and Thigh Muscle From Chicken, Turkey and Duck

Abstract: Lipid oxidation occurred rapidly in turkey muscle, intermediate in duck and slowest in chicken. pH was lowest in turkey muscle. Chicken muscle had a lower content of polyunsaturated fatty acids compared with turkey and duck muscles. The aqueous fraction of duck breast inhibited hemoglobin‐mediated lipid oxidation in washed muscle more effectively than aqueous fractions from turkey and chicken muscle. α‐Tocopherol content was highest in duck muscle, intermediate in chicken and lowest in turkey. Depletion of toc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…1). These results were also observed in the studies by Gong, Parker, and Richards (2010) in analyses on duck breast and thigh meat and by Alasnier, Meynier, Viau, and Gandemer (2000) in evaluations on lipid oxidation in chicken breast and thigh muscles. Part of the explanation for this probably involves the high pH of chicken thigh, and this may be the factor that slowed lipid oxidation during refrigerated storage, compared with chicken breast.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…1). These results were also observed in the studies by Gong, Parker, and Richards (2010) in analyses on duck breast and thigh meat and by Alasnier, Meynier, Viau, and Gandemer (2000) in evaluations on lipid oxidation in chicken breast and thigh muscles. Part of the explanation for this probably involves the high pH of chicken thigh, and this may be the factor that slowed lipid oxidation during refrigerated storage, compared with chicken breast.…”
Section: Resultssupporting
confidence: 76%
“…Part of the explanation for this probably involves the high pH of chicken thigh, and this may be the factor that slowed lipid oxidation during refrigerated storage, compared with chicken breast. Elevated pH decreases the ability of metals and heme proteins to oxidize lipids (Gong et al, 2010). In addition, Alasnier et al (2000) suggested that even though thigh muscles contained more pro-oxidant agents such as iron and potential substrate, the antioxidant status of thigh muscles represented by vitamin E and the antioxidant system (such as glutathione and antioxidant enzymes) remained efficient during the first stage of storage, such that they slowed down the rate of lipid oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to catalase, glutathione peroxidase also removes H 2 O 2 resulting water and oxidized glutathione. Furthermore, the hydroperoxides could be reduced by this enzyme activity, resulting in the formation of alcohol, water and oxidized glutathione [6,52,113].…”
Section: Factors Affecting Lipid Oxidationmentioning
confidence: 99%
“…Turkey muscle is more deficient in tocopherol (vitamin E) compared to chicken muscle (Mecchi et al, 1956). Other factors that may cause lipids in turkey muscle to rapidly oxidize include lower post mortem pH in turkey compared to chicken, more unsaturated fatty acids in turkey compared to chicken, and a deficiency of antioxidants in the aqueous phase of turkey muscle compared to duck muscle (Gong et al, 2010). A particularly rapid discoloration of turkey muscle was observed compared to pork muscle (Trout, 1990).…”
Section: Turkey Musclementioning
confidence: 99%